Developing Educational Videos Containing Authentic Interaction Video Clips for Teaching Language Functions - Indah Tri Purwanti; Eliwarti Eliwarti; Atni Prawati; Rumiri Rotua Aruan (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Videos containing authentic interaction-based video clips play an important role in facilitating EFL learners to study the target language. This study aimed to develop video lectures containing authentic interaction-based video clips, which can facilitate students in learning requests and apology speech acts. This study employed Research and Development using the ADDIE model. The analysis phase showed that it is necessary to develop the videos. Experts’ evaluations showed that the videos were acceptable, relevant, usable, and appropriate to a very high extent. The students’ evaluation revealed that the videos were valid and applicable to a high extent. In the implementation of the videos, it was revealed that there was a significant increase in the students’ ability. This means that the content of the videos was significant to increase the students’ ability. This means that the products of this research can be applied as lecture videos or instructional devices in teaching and learning devices for independent study.